Penyuluhan Hukum Tentang Pencegahan dan Penanganan Pornografi Anak di Lingkungan Sekolah ditinjau dari Peraturan Perundang-Undangan Yang Berlaku - Umi Muslikhah; Halimah Nur Izzati; Icha Herawati (I-Com: Indonesian Community Journal, 2025)
ABSTRACT One is to create and maintain an order of human life that has good behavior, good personality, applies the values ​​of the Almighty God, and honors and respects humanity. In its development, pornography has experienced rapid growth and distribution in line with the development and progress of information and communication technology. The circulation and dissemination of pornographic films is now increasingly rapid because it is supported by sophisticated information and communication facilities, one of which is the internet media which can be accessed by the public at any time. In the Information and Electronic Transactions (ITE) laws and regulations, one of the types of legal crimes in cyberspace is widespread violations of website content. One form of violation of website content is pornography. Pornography is the most common violation in Indonesia, by displaying pictures, stories or moving images. The issue of pornography being correlated with children has been carried out. A good personality will enable children to choose good behavior and not fall into negative behavior such as pornographic behavior. Keywords: Prevention; Handling; Child Pornography.